Single center outcomes of laparoscopic transperitoneal lateral adrenalectomy – Lessons learned after 500 cases: A retrospective cohort study. (August 2015) - Pędziwiatr, Michał; Wierdak, Mateusz; Ostachowski, Mateusz; Natkaniec, Michał; Białas, Magdalena; Hubalewska-Dydejczyk, Alicja; Matłok, Maciej; Major, Piotr; Budzyński, Piotr; Migaczewski, Marcin; Budzyński, Andrzej
Abstract: Introduction: Although laparoscopic adrenalectomy is considered relatively safe, the results of treatment vary depending on the profile of the hospital. We would like to present our experience with laparoscopic surgery of the adrenals. Methods: We conducted a retrospective cohort study of consecutive patients operated for adrenal tumours in the years 2003–2014. The study group included 175 (35%) men and 325 (65%) women. The entire group was divided into 4 cohorts of 125 consecutively operated patients. Primary outcomes were operative measures (operative time, its correlation with tumour size, blood loss, conversion rate, use of peritoneal drainage). Secondary outcomes were the intra- and postoperative complications (using the Clavien-Dindo classification), histological type of the tumours and length of hospital stay. Results: There were no differences between groups in terms of the size and location of the tumour. The mean operative time in each group was 85.7; 83.7; 89.6; 104.6 min (p < 0.001). The operative time correlated to the size of the tumour. There were no differences in the conversion rates as well as in the blood loss. However, it was observed that the complication rate was declining in subsequent subgroups (14.4%, 11.2%, 8% and 5.6%, respectively, p = 0.013). Length of hospital stay was 4.9 days, 3.9 days, 2.9 days, 2.4 days, respectively (p < 0.001). Conclusion: The results of laparoscopic adrenalectomy depend not only on the experience of the single surgeon, but on the whole team involved in perioperative care. In high volume centers with extensive experience in surgery of adrenals, this technique may provide an alternative to open surgery, also in selected cases of malignant tumours. Highlights: The outcomes of laparoscopic transperitoneal lateral adrenalectomy depend on the volume of the department. Gaining the experience with laparoscopic adrenalectomy reduces complication rate and shortens length of hospital stay. Involving surgery residents in training is associated with longer operative time but with no impact on clinical outcomes.